Organizational Principles of the Financial Reporting Audit in Ukraine - Lubenchenko, O. E.; Vasiliuk М. М. (Statistics of Ukraine, 2019)
The steps to organize the work of an audit firm on performing the task of obligatory audit of financial reporting are defined: (i) appoint the key partner in the audit considering the criteria of audit quality, independence and competency; (ii) record the revealed non-compliances with the Law of Ukraine “Audit of Financial Reporting and Auditing Activities” in the work of an audit firm; (iii) make up personal records of audit customers; (vi) make up working documents, including the ones confirming independence of an audit firm and its staff, conclusions made in time of audit, to produce the audit report; (v) consider the specifics of actions of the key partner in audit in checking the consolidated financial report, the interactions with the Inspection on Quality Assurance, which is a part of the Body charged with public supervision of auditing and the Audit Chamber of Ukraine. It is found that more than one key partner can be appointed according to the Ukrainian law. This situation is fully acceptable when financial reports of high structured economic entities making up consolidated reporting are audited. It is substantiated that the key partner in audit and task teams members are appointed by an administrative document (the order) of an audit firm. The latter are appointed after the assessment of resources (human and technical) necessary for the task completion at the phase of client acceptance, which can be subject to subsequent review at the phases of planning and task performing, with the respective change in the team staff. An example of calculating the time budget for the audit task completion is provided. It is emphasized that a change of the key partner in time of audit would not be reasonable, because it is stipulated in the law that such partner must be personally involved in checking and sign the auditor report when the check is over. A change of the key partner will decline the quality of financial reporting audit due to the lack of permanent supervision over the checking process and control of task team members, especially when contradictory issues have to be dealt with. An audit firm can reveal non-compliances of its practices with the requirements of the Law of Ukraine “Audit of Financial Reporting and Auditing Activities” and introduce the procedures of recording the revealed non-compliances. These non-compliances are systematized in the article. A format of the personal records of audit customers and sources of making up personal records are specified. A format of the book for analysis of complaints coming from customers and regulatory bodies is proposed to audit firms. The recommended measures can help assure the quality of financial reporting audit in Ukraine.